The impulse toward the disadvantaged in the gospel preached by Paul: an analysis of 1 Corinthians 1:10-4:21 and 8:1-11:1 - Ellington, Dustin Watson (Scriptura, 2016)
This article examines two major sections of 1 Corinthians, 1:10-4:21 and 8:1-11:1, arguing that we find within Paul’s gospel of Christ crucified an impulse to elevate the position of the disadvantaged members of the Corinthian congregation. In both sections the gospel serves as Paul’s resource for working toward just and unified relations. The study of 1 Cor. 1:10-4:21 traces the apostle’s own identification with the cross and with disadvantaged members of the church. Paul’s call to imitate himself becomes a means of imparting to the whole congregation a new identity as a people of power, as they embrace the way of the cross and the apostles. The reading of 1 Cor. 8:1-11:1 exhibits Paul’s use of Christ’s death for the ‘weak’ as a model for his own personal adjustments on behalf of the gospel and in deference to the vulnerable. By imitating Paul, the Corinthians can work with - not against - the gospel’s impulse to honour the disadvantaged.